2016
DOI: 10.1016/j.jsbmb.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vitamin D receptor expression by retinoic acid receptor alpha in acute myeloid leukemia cells

Abstract: Acute myeloid leukemia (AML) is the predominant acute leukemia among adults, characterized by an accumulation of malignant immature myeloid precursors. A very promising way to treat AML is differentiation therapy using either all-trans-retinoic acid (ATRA) or 1,25-dihydroxyvitamin D3 (1,25D), or the use of both these differentiation-inducing agents. However, the effect of combination treatment varies in different AML cell lines, and this is due to ATRA either down- or up-regulating transcription of vitamin D r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Together, these results indicate a putative RA/c-Raf/GSK-3/RARα axis that is susceptible to RRD-251 and represents a novel regulatory pathway for RA differentiation that may extend its utility beyond APL to other myeloid leukemias. Additionally RRD-251 may have further potential in combination therapies for leukemic differentiation utilizing 1,25-dihydroxy vitamin D3 as GSK-3 and RARα were recently found to regulate VDR expression and transcriptional activity [41-43]. …”
Section: Discussionmentioning
confidence: 99%
“…Together, these results indicate a putative RA/c-Raf/GSK-3/RARα axis that is susceptible to RRD-251 and represents a novel regulatory pathway for RA differentiation that may extend its utility beyond APL to other myeloid leukemias. Additionally RRD-251 may have further potential in combination therapies for leukemic differentiation utilizing 1,25-dihydroxy vitamin D3 as GSK-3 and RARα were recently found to regulate VDR expression and transcriptional activity [41-43]. …”
Section: Discussionmentioning
confidence: 99%
“…It is known that RXRs heterodimerise with both RARs and NR4A receptors, but RARs and NR4A receptors do not heterodimerise to one another. Currently, there is no literature relating the RARs directly with the NR4As, in particular NR4A2, although a recent study has found that RARs regulate VDR transcription [71]. This hemispheric asymmetry supports findings of the left hemisphere being more pathologically impaired in schizophrenia compared to the right [68-70].…”
Section: Discussionmentioning
confidence: 67%
“…Past research indicated a synergistic cancer differentiation effect by using a combination of 1,25D and ATRA [11]. However, our recent experiments have revealed that in AML cell lines the effect of combination treatment varies, due to either down- or upregulation of VDR expression in response to ATRA, depending on the AML cell line examined [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Our recent experiments have revealed a new exon, 1g, regulated from the promoter of exon 1a. Exon 1g is used in VDR transcripts present in AML cells [13]. Multiple publications confirm that VDR expression in humans is regulated in response to ATRA [12,21,22,23], while there are conflicting reports concerning regulation of human VDR by 1,25D [13,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation